Mapeamento de epítopos da crotoxina, principal neurotoxina do veneno de Crotalus durissus terrificus (cascavel sul americana) - Denis Alexis Molina Molina (2017)
Crotoxin (CTx) is a dimeric protein that is responsible for the neurotoxic activity of Crotalus durissus terrificus venom. In this work we have used 3 different techniques for mapping of linear epitopes of the Crotoxin B cells. The three methods were: Prediction by bioinformatics, Spot-Synthesis method and mapping by subcutaneous implants of peptides in mice. Sera of horses immunized with the total venom of C. d. terrificus were used in the Spot-Synthesis method. Immunoassays in the Spot-Synthesis method have shown that the C-terminal region of each of the CTx subunits is a dominant immunogenic region. These results were similar to the ones obtained by the bioinformatic method. Mapping by subcutaneous implants has identified other immunodominant regions of the crotoxin. The previously identified amino acid sequences corresponding to the immunogenic regions were chemically synthesized and the purity of these peptides were evaluated by mass spectrometry. The synthetic peptides were antigenically characterized by immunoblot using anticrotalic horse serum, for the immunogenic characterization of peptides, they were polymerized with glutaraldehyde and used as immunogens in the immunization of mice. Anti-peptide anti-mouse antibodies recognized CTx, the total venom of C. d. Terrificus and the synthetic peptides.All epitopes were found in the CTx 3D structure and they are located on the surface of the protein